Comparative Trends in Political Culture: A Study of Western Nations & Bangladesh - Rafia Tasnim Setu; Mahmud , Md. Sultan; Arafat, Md. Yeasir; Alam , Md. Mahbubul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Political culture is the shared beliefs, values, and attitudes of people about politics and government. It examines public attitudes towards democracy and government. The objectives of this research article are to compare political culture in Western nations and government with that of Bangladesh. The political cultures of Western democracies, such as the U.S. and European nations, are characterized by individualism, secularism, and a strong emphasis on democratic norms. In contrast, Bangladesh exhibits a more collectivist political culture, influenced by its colonial history, cultural traditions, and the challenges of a developing nation. This paper highlights the impact of these cultural differences on political participation, trust in government, and policy outcomes. The study finds that Western nations often exhibit higher political participation, trust in institutions, and a stronger sense of individual political rights. In contrast, Bangladesh shows more collective political engagement, influenced by social hierarchies, historical legacies, and political instability. The role of media in shaping political discourse also varies, with Western nations benefiting from diverse media outlets, while Bangladesh’s media is often constrained by political pressures. These differences reflect how culture and history shape distinct political attitudes and behaviors in both regions. Furthermore, it uses a qualitative approach, relying solely on secondary data sources such as academic articles, reports, and surveys to examine political culture trends. No primary data collection is involved.